Targeting protein kinase B/Akt signaling with vanadium compounds for cardioprotection - Bhuiyan, Md Shenuarin; Shioda, Norifumi; Fukunaga, Kohji (Expert opinion on therapeutic targets, 2008)
Akt is an important signaling molecule that modulates many cellular processes such as cell growth, survival and metabolism. Akt activation has been proposed as a potential strategy for increasing cardiomyocyte survival following ischemia. Vanadium compounds activate Akt signaling through inhibition of protein tyrosine phosphatases, thereby eliciting cardioprotection in myocardial ischemia/reperfusion-induced injury along with cardiac functional recovery. Like other vanadium compounds, we documented bis(1-oxy-2-pyridinethiolato) oxovanadium (IV) as a potent cytoprotective agent on myocardial infarction and elicited cardiac functional recovery through activation of Akt signaling pathway. The ability of vanadium compounds to activate Akt signaling pathways are responsible for their ability to modulate cardiovascular functions and is probably beneficial as a cardioprotective drug in subjects undergoing reperfusion therapy following myocardial infarction.